VOICE OF MALAYSIA AS MEDIA IN MANAGING THE PROPAGANDA IN MALAYSIA- INDONESIA CONFRONTATION (1963-1965) - Ghani, Rohani Hj. Ab; Mustaffa, Chesu (CENTRAL ASIA AND THE CAUCASUS, 2021)
Mass media played a significant role in conveying a government’s information to the society. At international level, the mass media is very effective in highlighting the image of the country and in the early years of Malaysia’s independence, this role was entrusted to Suara Malaysia Broadcast. The history of the establishment of Voice of Malaysia is closely related to the Malaysia’s confrontation with Indonesia (1963-1966). With the necessity of Malaysian security, the Voice of Malaysia formed to against Sukarno’s propaganda towards Malaysia. This paper discusses the history of the formation of the Voice of Malaysia and its role as counter attack of Indonesia’s black propaganda. Through the Voice of Malaysia, the Malaysian government has channeled current economic, political and social situation during Confrontation period. The most interesting aspect was the Voice of Malaysia also involved the Indonesian peoples who fled to Malaysia for opposing Sukarno. Finally, Confrontation was successfully ended through Bangkok Treaty 1966. The effectiveness of the Voice of Malaysia was acknowledged by British representatives and Indonesian military leaders. This paper uses the classical diplomatic historical approach and qualitative method. Most of the references are based on British official records gathered from the British National Archive, Kew, London. Other references are secondary resources such as books and article. The major finding of this paper is proved that the significant role mass media as a non-military instrument in against outside threat.